Meta Analisis Efektivitas Pelatihan Online dalam Meningkatkan Kompetensi Pedagogik Guru - Rochmah, Luthfi Maulida; Narmayani, Narmayani; Muzekki, Taufikur Rohman; Sobri, Ahmad Yusuf; Ubaidillah, Aan Fardani (Proceedings Series of Educational Studies, 2024)
Abstract : This study aims to determine the effectiveness of online training for teachers in improving pedagogical potential. The method in this study uses meta-analysis which is conducted by reviewing research results relevant to the research variables from various research articles. The purpose of meta-analysis is to obtain more valid and reliable results by synthesizing the results of many different studies conducted.  By conducting research on articles published in national journals related to Training and Development in improving teacher pedagogics. Data was collected by searching electronic journals and using the keywords "Online training", "Effectiveness" and "Improving teachers' pedagogical competence" on Google Scholar. From the search, 60 articles from journals were obtained. The results of the meta-analysis from national journals show that online teacher training is effective in improving teachers' pedagogical competence. Through the online platform, teachers can access training materials anytime and anywhere, allowing them to learn according to their personal time and needs. The presence of diverse resources, interactive modules and online discussion forums also support collaboration and exchange of experiences between teachers.Abstrak : Penelitian ini bertujuan untuk mengetahui efektivitas pelatihan online untuk guru dalam meningkatkan kompetensi pedagogik. Metode dalam penelitian ini menggunakan meta-analisis yang dilakukan dengan mengkaji hasil penelitian yang relevan dengan variabel penelitian dari berbagai artikel penelitian. Tujuan dari meta-analisis adalah untuk memperoleh hasil yang lebih valid dan dapat diandalkan dengan mensintesis hasil dari banyak penelitian berbeda yang dilakukan.  Dengan cara melakukan penelitian terhadap artikel-artikel yang dipublikasikan di jurnal nasional yang berkaitan dengan Pelatihan dan Pengembangan dalam meningkatkan pedagogik guru. Data dikumpulkan dengan mencari jurnal elektronik dan menggunakan kata kunci "Pelatihan online”, “Efektivitas" dan "Meningkatkan Kompetensi pedagogik guru" di Google Scholar. Dari penelusuran itu diperoleh 60 artikel dari jurnal. Hasil meta-analisis dari jurnal nasional menunjukkan bahwa Pelatihan guru secara online terbukti efektif dalam meningkatkan pedagogik guru. Melalui platform online, guru dapat mengakses materi pelatihan kapan saja dan di mana saja, sehingga memungkinkan mereka  belajar sesuai  waktu dan kebutuhan pribadi mereka kehadiran beragam sumber daya, modul interaktif, dan forum diskusi online juga mendukung kolaborasi dan pertukaran pengalaman antar guru.